The Role of Husbands in Childbirth: A Strategic Approach to Enhancing Maternal Care Quality - Rita Dewi Sunarno; Dian Sulistiyaningsih (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: The quality of maternal healthcare is influenced not only by medical treatments but also by the emotional and social support provided during childbirth. Involvement of husbands as birth companions has been shown to improve maternal experiences and delivery outcomes. Objective: This study to analyze the role of husband involvement during labor as a strategic approach to improving maternal care quality, with particular focus on maternal psychological well-being and perception of health services. Methods: A quasi experimental design with a pre and post-test control group was used. A total of 100 participants without structured husband participation were selected through purposive sampling and divided two groups: 50 in the intervention group where husbands were actively involved as birth companions, and 50 in the control group, which received standard maternal care. Data were collected using a structured questionnaire. Results: The intervention group showed a significant increase in post-test scores (mean = 41.50 ± 5.40) compared to their pre-test scores (32.80 ± 6.20), confirmed by paired t-test (t = 15.20, p < 0.001). The control group also improved slightly (mean = 36.70 ± 6.10; t = 4.30, p = 0.001). Post-test comparison using independent t-test showed a significant difference between the two groups (t = 11.80, p < 0.001). Conclusion: Husband involvement during childbirth significantly enhances maternal care quality, improves psychological well-being, and increases satisfaction with health services. These findings support strategies to promote husband participation during labor.